2013
DOI: 10.1136/jech-2012-201096
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evidence on association between ambient air pollution and stroke mortality

Abstract: This study provides new evidence for the association between exposure to ambient air pollution and stroke mortality. Our results also suggest that underlying cardiac disorder may increase the risk for ischaemic-stroke mortality in relation to air pollution exposure, especially NO2. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 41 publications
(15 reference statements)
6
50
2
Order By: Relevance
“…These transient increases in risk immediately after PM exposure are supported by experimental studies demonstrating that inhalation of diesel exhaust caused vascular dysfunction, ischemia, and thrombotic dysfunction within few hours after exposure. 15,22 The elevated risk of hemorrhagic stroke (ie, 2 to <4 hours as well as 48 to <72 hours before the event) is consistent with previous studies in Asian countries [8][9][10][11][12][13] and may be explained by the high frequency of hemorrhagic stroke in these countries, including Japan. 7 The present finding of slightly higher and persistently elevated risk of hemorrhagic stroke compared with ischemic stroke or TIA may be attributable to differences in the mechanisms of hemorrhagic stroke and ischemic stroke/TIA.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These transient increases in risk immediately after PM exposure are supported by experimental studies demonstrating that inhalation of diesel exhaust caused vascular dysfunction, ischemia, and thrombotic dysfunction within few hours after exposure. 15,22 The elevated risk of hemorrhagic stroke (ie, 2 to <4 hours as well as 48 to <72 hours before the event) is consistent with previous studies in Asian countries [8][9][10][11][12][13] and may be explained by the high frequency of hemorrhagic stroke in these countries, including Japan. 7 The present finding of slightly higher and persistently elevated risk of hemorrhagic stroke compared with ischemic stroke or TIA may be attributable to differences in the mechanisms of hemorrhagic stroke and ischemic stroke/TIA.…”
Section: Discussionsupporting
confidence: 77%
“…[4][5][6] Several studies in Asian countries, where the incidence of hemorrhagic stroke is high, 7 have suggested an association between air pollutant levels and this type of stroke. [8][9][10][11][12][13] In addition, most studies to date have evaluated the association between daily time scale of air pollution and cardiovascular outcomes. Only a small number of epidemiological studies have examined the effect of hourly variations in air pollution on ischemic heart disease, 1,14 cardiac arrest, 3 or ischemic stroke 5,6 and demonstrated possible adverse effects.…”
mentioning
confidence: 99%
“…Modifiers at individual level on pollution associated mortality have been examined in previous studies (Bell et al, 2013;Cakmak et al, 2011;Forastiere et al, 2005;Ou et al, 2008;Peel et al, 2007;Qian et al, 2013;Ren et al, 2010;Zanobetti et al, 2000;Zanobetti and Schwartz, 2002;Zeka et al, 2006). There was strong and consistent evidence that elderly experience higher risk of pollution associated mortality (Bell et al, 2013;Cakmak et al, 2011;Forastiere et al, 2005;Zanobetti and Schwartz, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…The concentration of 7 pollutants including SO 2 , NO 2 , O 3 , CO, PM 10 , NO X , and NO are measured daily in Kerman by a fixed station. The urban monitoring stations in Kerman uses the Beta-ray absorption method for measuring the concentration of PM 10 , UV fluorescence for SO 2 , chemical luminance for NO, NO 2 and NO X , non-diffraction infrared absorption (NDIR) for CO and UV absorption for measuring the concentration of O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In the recent years, human's activities have made alarming changes in ambient air pollutants that lead to climate change and serious health consequences [3] . Air pollution is nowadays the most critical environmental challenge and can increase cardiovascular, respiratory and many more diseases [4] .…”
Section: Introductionmentioning
confidence: 99%